GAMBARAN EFEK SAMPING OBAT ANTI TUBERKULOSIS (OAT) LINI KEDUA PADA PASIEN TUBERCULOSIS-MULTIDRUG RESISTANCE (TB-MDR) DI POLIKLINIK TB-MDR RSUD ARIFIN ACHMAD PROVINSI RIAU - Qurratul Aini; Indra Yovi; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTMultidrug resistant tuberculosis (MDR-TB) is one of tuberculosis resistance to at leasttwo anti tuberculosis drugs rifampicin and isoniazide. Second line drugs used in MDRTBtreatment had a greater toxicity compared with first line and a lot of adverse event, itcauses patient would have symptoms of side effect during treatment . The purpose of thisresearch had to know adverse event of second line anti-TB drug in MDR-TB patient inMDR-TB polyclinic Arifin Achmad General Hospital of Riau Province. This research wasused as mixed methods with quantitative and qualitative approachment. Adverse eventwas also discussed in qualitative data as a complement. Samples in this research wereobtained by total sampling method as many as 12 MDR-TB patient were diagnosedbetween April 2013 to Juni 2014 . Quantitative study results showed that adverse eventwere experienced by 100% patient. Prevalence of nausea and vomiting was 100%,headache 100%, arthralgia 91,67%, injected location pain 91,67%, peripheralneuropathy 83,33%, depression 83,33%, sleep disturbance 83,33%, allergic reaction75%, anorexia 75%, gastritis 66,67%, hearing distrubance 66,67%, vertigo 58,33%,tendinitis 58,33%, psychosis 50%, visual disturbance 50%, minor electrolite disturbance(hypokalemia) 41,67%, diarrhea 16,67%, severe electrolite disturbance 16,67%, gasterbleeding 8,33%. Qualitative study results showed that patient had difference adverseevent experienced. Management of adverse event by clinical officer in MDR-TBpolyclinic have done their duty based on standart operational procedures.Key word: multidrug resistant tuberculosis (MDR-TB), adverse event of second line anti-TB drug, adverse event of MDR-TB treatment.